Home culture and its effects on English as a lingua franca communication: Voices from Chinese students at a United Kingdom university - Zhang, Xiao; Lütge, Christiane (Frontiers in Psychology, 2023)
In academic research on intercultural communication (IC), students’ perceptions and experiences regarding English as a lingua franca (ELF) have been central to the discussion because they form the basis for English teaching policies and practices in multilingual and multicultural environments. Substantial theoretical research on ELF has called for a paradigm shift from emphasizing the over-simplistic correlation between language and Anglophone cultures to recognizing the legitimacy of non-native English learners’ home culture in English teaching pedagogy. Nonetheless, little empirical research has been conducted to examine how ELF speakers understand their home culture in ELF communications. Relatively fewer studies have investigated to what extent ELF users’ perceptions of home culture influence their IC practices. To address these gaps, this study aims to explore Chinese international students in a liberal arts university in the United Kingdom and their understanding of Chinese culture in authentic ELF interactions. In addition, the perceived effects of Chinese culture on students’ IC were explored in great depth. This study adopts a mixed-method approach, including a student questionnaire (N = 200) and follow-up semi-structured interviews (N = 10). Following descriptive statistics and thematic analysis of the obtained data, the findings revealed that most participants lacked a thorough understanding of their home culture, while they considered home culture playing a significant role in ELF communications. The contribution of this study builds on work in English users’ awareness of home culture in IC to identify the significance of enabling the presence of English learners’ home culture in English language teaching (ELT) classrooms.